International negotiation : a process of relational governance for international common interest / Evangelos Raftopoulos. - Raftopoulos, Evangelos (Cambridge studies on environment, energy and natural resource governance., 2019)
Evangelos Raftopoulos explores international negotiation as a structured process of relational governance that generates international common interest between and among international participants and in relation to the international public order. He challenges prescriptive models of negotiation - developed in international relations and positivistic approaches to international law, which artificially separate treaties from negotiation in the name of 'objectivity' - and opens a window for looking at international negotiations from a novel, international law perspective. Using an interdisciplinary approach that incorporates law, philosophy, politics, and linguistics, he proposes a holistic, theoretical model of multilateral international negotiation that not only offers a 'subjective' view of international law in practice but also demonstrates the importance of understanding the horizontal normativity of international ordering. This work should be read by academics and practitioners of international law and negotiations, officials of international organizations, and anyone else interested in international law and international relations.